2010
DOI: 10.1002/asia.201000569
|View full text |Cite
|
Sign up to set email alerts
|

Aryl Azide Based, Photochemical Patterning of Cyclic Olefin Copolymer Surfaces with Non‐Biofouling Poly[(3‐(methacryloylamino)propyl)dimethyl(3‐sulfopropyl)ammonium hydroxide]

Abstract: Micropatterns of cells were generated on a cyclic olefin copolymer (COC) by a combination of aryl‐azide‐based photopatterning of a polymerization initiator and surface‐initiated atom‐transfer radical polymerization of non‐biofouling 3‐(methacryloylamino)propyl)‐dimethyl(3‐sulfopropyl)ammonium hydroxide (MPDSAH). The optical transparency of the COC made it possible to generate the patterns indirectly through a COC slab.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 74 publications
1
14
0
Order By: Relevance
“…After photografting of the initiator 1 , the static water contact angle changed to 39° from 95°, which indicated the successful anchoring of 1 onto the COC surface under the UV irradiation conditions (Figure 1 a). 8 The water contact angle increased slightly to 44° after SI‐ATRP, which corresponds closely to that of a p OEGMA film on gold 10. The XPS characterizations further confirmed the successful modifications of the COC surface at each step.…”
Section: Methodssupporting
confidence: 58%
See 2 more Smart Citations
“…After photografting of the initiator 1 , the static water contact angle changed to 39° from 95°, which indicated the successful anchoring of 1 onto the COC surface under the UV irradiation conditions (Figure 1 a). 8 The water contact angle increased slightly to 44° after SI‐ATRP, which corresponds closely to that of a p OEGMA film on gold 10. The XPS characterizations further confirmed the successful modifications of the COC surface at each step.…”
Section: Methodssupporting
confidence: 58%
“…In this respect, some attempts have been made to simply change the surface hydrophobicity by methods such as physical adsorption and chemical oxidation 5c. 7 To minimize biofouling in a more chemically controlled fashion, we have recently applied an aryl azide‐based photoreaction to a COC surface to coat it with a nonbiofouling polymer, poly[(3‐(methacryloylamino)propyl)‐dimethyl(3‐sulfopropyl)ammonium hydroxide] 8. Herein, we extended our aryl azide‐based strategy to chemical functionalization of the COC surface with a post‐functionalizable and nonbiofouling polymer, poly(oligo(ethylene glycol) methacrylate) ( p OEGMA).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This indicated that the contribution of surface functionalization is based on the photochemical reaction, rather than physical adhesion via π‐π stacking. As per a previous report, it is regarded that photolysis of the aryl azide generated a reactive nitrene, which functionalized the hydrocarbon based plastic surfaces …”
Section: Acknowledgmentsmentioning
confidence: 81%
“…The overall coating process to obtain a non‐fouling PET substrate is summarized in Figure . First, we used an aryl azide‐based initiator (ABI) that has been utilized for the surface functionalization of chemically inert plastics . Since the PET substrate itself contains aryl moieties, we reasoned that UV irradiation may not be necessary to immobilize ABI on the PET surface, because physical adhesion via π‐π stacking might be sufficient.…”
Section: Acknowledgmentsmentioning
confidence: 99%